High On-Treatment Platelet Reactivity in Danish Hyper-Acute Ischaemic Stroke Patients - Rath, Charlotte L.; Rye Jørgensen, Niklas; Wienecke, Troels (Frontiers in Neurology, 2018)
Objective: Early anti-platelet therapy is a cornerstone in the prevention of recurrent ischaemic stroke (IS) and transient ischaemic attacks (TIAs), although the responsiveness to anti-platelet medications varies among patients. Several studies have reported that patients with ischaemic stroke who exhibit high on-treatment platelet reactivity (HTPR) 5-10 days after antiplatelet medication onset, have an increased risk of vascular events. In this study we aim to determine the prevalence of HTPR in the hyper-acute stroke phase less than 48 hours from symptom onset, after the administration of a 300-mg bolus of oral clopidogrel in a real-world setting in Danish IS and TIA patients. Material and methods: In total, 219 Danish patients with acute IS or TIA received 300 mg of oral clopidogrel on admission. Blood samples from all patients were analysed using the VerifyNow P2Y12 system at 8–24 h after clopidogrel intake. Concomitant therapy and the intervals between ictus and blood collection, clopidogrel intake and blood collection, and blood sampling and analysis were recorded for all patients. Results: HTPR in the hyper-acute stroke phase was observed in 28.8% (63/219) samples. After adjustment for age, sex, co-morbidities, and co-medications, none of the tested variables exhibited an association with HTPR or the platelet reaction unit value measured using the VerifyNow P2Y12 system. Conclusions: The recognition of HTPR to specific anti-platelet agents in the hyper-acute phase after stroke may be the first step towards interventions that may further minimize the early recurrent stroke risk. Further large randomized trials including clinical outcome assessments are necessary.